STUDY OF CLINICOPATHOLOGICAL PROFILE OF PANCYTOPENIA PATIENTS OF SOUTHERN RAJASTHAN - ANKIT AGARWAL; AVI SHAH; RENU MISHRA; DIVYANG PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To study clinical presentation, demographic profile, and hematopathological profile of pancytopenia patients. Methods: An observational, cross-sectional study was conducted at Geetanjali Medical College, and Hospital from September 2022 to September 2023 on patients presenting with pancytopenia. Results: A total of 150 patients diagnosed with pancytopenia participated in the study, comprising 84 males and 66 females, with the average age of the participants being 44.90 years. The most common etiology of pancytopenia was megaloblastic anemia, followed by hematological malignancy. Hematological malignancies were observed in 24 patients. The most common cause of hematological malignancy was non-Hodgkins lymphoma followed by plasma cell dyscrasias. Out of 150 pancytopenia study participants, 110 participants had bone marrow examination. The most common observed bone marrow examination finding was hypercellular bone marrow seen in 80 (72.73%) patients. Conclusion: From our study, it can be proposed that despite numerous etiologies available for pancytopenia and its various manifestations, the most common etiology is megaloblastic anemia. Physical findings, complete blood count, and peripheral blood smear examination provide valuable information in the initial workup of the patients presented with pancytopenia and can provide valuable clues to underlying etiology. Bone marrow examination is a gold standard investigation for comprehensive evaluation of pancytopenia and guides further management in these cases.